RURAL YOUTH BEHAVIOR IN WATCHING TELEVISION (Case Study Rural Youth in Ciasmara Village Pamijahan Sub-District, Bogor Regency) - Yogaprasta Adi Nugraha; David Rizar Nugroho (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
Family is an important social unit that forming youth identity, but in the other hand family is also a place where contestation happened. Power-relation inside family is commonly happened during several activities such as watching television, having dinner, and prior go to school. The objective of this research is to unmasking the reality of power relation in television watching activities. Qualitative method is used to dissect this phenomenon. In the context of families that only have one television, power relation in watching television is inevitable, especially the prime time, because at this time all family members watch television. This study found that there are several actors who hold important role in power relation, such as Little brother, Grandma, and Father. Their domination have made rural youth become marginalized on their own house